2021
DOI: 10.3390/antiox10040625
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Vascular Dysfunction, Oxidative Stress, and Inflammation Are Improved by Pharmacological Modulation of the NRF2/HO-1 Axis

Abstract: Vascular oxidative stress, inflammation, and subsequent endothelial dysfunction are consequences of traditional cardiovascular risk factors, all of which contribute to cardiovascular disease. Environmental stressors, such as traffic noise and air pollution, may also facilitate the development and progression of cardiovascular and metabolic diseases. In our previous studies, we investigated the influence of aircraft noise exposure on molecular mechanisms, identifying oxidative stress and inflammation as central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…The lack of further deterioration of endothelial function may indicate that there is a mitigating mechanism ("rescue" pathway) that prevents the observed further increases in oxidative stress within the vasculature being translated into a further deterioration of vascular function. We have previously reported that transcription factor Nrf2 may represent an important defense system for preventing the cardiovascular effects noise and that the expression of a down-stream target of Nrf2, heme oxygenase 1, is also induced by noise exposure while concentrations of its antioxidant product bilirubin are diminished (Jimenez et al, 2021). Therefore, it seems likely that an additional antioxidant mechanism may exist that mitigates further exacerbation of a stressed phenotype.…”
Section: Consequences Of Chronic Noise Exposure On Oxidative Stress and Inflammationmentioning
confidence: 99%
“…The lack of further deterioration of endothelial function may indicate that there is a mitigating mechanism ("rescue" pathway) that prevents the observed further increases in oxidative stress within the vasculature being translated into a further deterioration of vascular function. We have previously reported that transcription factor Nrf2 may represent an important defense system for preventing the cardiovascular effects noise and that the expression of a down-stream target of Nrf2, heme oxygenase 1, is also induced by noise exposure while concentrations of its antioxidant product bilirubin are diminished (Jimenez et al, 2021). Therefore, it seems likely that an additional antioxidant mechanism may exist that mitigates further exacerbation of a stressed phenotype.…”
Section: Consequences Of Chronic Noise Exposure On Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Hahad et al, 2021a;Osborne et al, 2021). Noisemediated inflammation in mice was also prevented by genetic Nox2 deletion as shown by two independent preclinical studies (Kroller-Schon et al, 2018;Eckrich et al, 2021) and antioxidant pharmacological activation/induction of the Nrf2-HO1-axis (Bayo Jimenez et al, 2021).…”
Section: Noise Causes Activation Of the Phagocytic Nadph Oxidase With Subsequent Redox Activation Of Inflammatory Cellsmentioning
confidence: 86%
“…This is probably the reason, aside from stress hormone-dependent activation and infiltration of immune cells into the vasculature, for the observed noise-triggered inflammation in exposed mice ( Munzel et al, 2017 ; Kroller-Schon et al, 2018 ; Steven et al, 2020 ; Eckrich et al, 2021 ; Frenis et al, 2021 ) but also the shift to a pro-atherothrombotic phenotype of the plasma proteome of train noise-exposed healthy human subjects ( Herzog et al, 2019 ), epigenetic changes that promote immune cell activation and expression of CRP ( Cai et al, 2017 ; Eze et al, 2020 ) and amygdala activation driven coronary atherosclerosis ( Osborne et al, 2020 ; Hahad et al, 2021a ; Osborne et al, 2021 ). Noise-mediated inflammation in mice was also prevented by genetic Nox2 deletion as shown by two independent preclinical studies ( Kroller-Schon et al, 2018 ; Eckrich et al, 2021 ) and antioxidant pharmacological activation/induction of the Nrf2-HO1-axis ( Bayo Jimenez et al, 2021 ).…”
Section: Redox Switches Activated By Noise Exposurementioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, nuclear factor erythroid-2-related factor 2 (Nrf2) is responsible for the cellular response to oxidative stress. When it is activated by hemin, the expression of antioxidant enzymes in cells increases, and those can attenuate the oxidative stress caused by GOX or ultraviolet rays [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%